2003
DOI: 10.1111/j.1574-6941.2003.tb01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hot spring cyanobacteria to the mysterious deaths of Lesser Flamingos at Lake Bogoria, Kenya

Abstract: Cyanobacterial mats at hot springs on the shore of the alkaline Lake Bogoria, Kenya, were investigated regarding species community and cyanobacterial toxin content. The hepatotoxins microcystin-LR, -RR, -LF and -YR, and the neurotoxin anatoxin-a were present. The mats were dominated by Phormidium terebriformis, Oscillatoria willei, Spirulina subsalsa and Synechococcus bigranulatus. The concentration of microcystins in mat samples, ranged from 221 to 845 microg microcystin-LR equivalents g(-1) DW of mat. Anatox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(94 citation statements)
references
References 30 publications
2
87
1
4
Order By: Relevance
“…data 2007) in Lake Manyara reported microcystin concentrations of up to 1.1 lg/g dry weight (DW) of phytoplankton. This is supported by several other studies conducted in Kenya which reported high concentrations of microcystins and anatoxins from dead Lesser Flamingo tissue and cyanobacteria samples enough to cause Lesser Flamingo mortality Krienitz et al, 2003;Ballot et al, 2004). Other investigations in Kenyan alkaline saline lakes reported heavy metals (Kairu, 1996;Ndetei & Muhandiki, 2005) and pesticides (WWF-LNCDP, 1994;Nelson et al, 1998) as the cause of Lesser Flamingo mortalities.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…data 2007) in Lake Manyara reported microcystin concentrations of up to 1.1 lg/g dry weight (DW) of phytoplankton. This is supported by several other studies conducted in Kenya which reported high concentrations of microcystins and anatoxins from dead Lesser Flamingo tissue and cyanobacteria samples enough to cause Lesser Flamingo mortality Krienitz et al, 2003;Ballot et al, 2004). Other investigations in Kenyan alkaline saline lakes reported heavy metals (Kairu, 1996;Ndetei & Muhandiki, 2005) and pesticides (WWF-LNCDP, 1994;Nelson et al, 1998) as the cause of Lesser Flamingo mortalities.…”
mentioning
confidence: 73%
“…Microcystins analysis in the tissue samples was done at the Norwegian Veterinary Institute laboratory in Norway. The toxin extraction was done as described by Krienitz et al (2003). Three grams of tissue sample were minced in 10 ml of methanol and homogenized using a blender for 5 min under constant cooling, and centrifuged for 5 min at 5000 rpm.…”
Section: Microcystins Analysis In Lesser Flamingo Tissue Samplesmentioning
confidence: 99%
“…So far, D. fontinale has only been detected in warm springs, and not in the numerous hot springs found within the vicinity to the locus classicus. Interestingly, the cyanobacterial flora of these hot springs is quite different from that of the warm springs (hinDáK 2001; Krienitz et al 2003;DaDheech et al 2013b). Based on our observations, it is clear that mandatory presence of gas vesicles in the cells for characterization of the genus Desertifilum needs revision.…”
Section: Discussionmentioning
confidence: 99%
“…It has since been identified in the benthic species Aphanizomenon issatschenkoi in New Zealand (Wood et al, 2007). Additionally, until recently anatoxin-a production was not found on any continent that was once a part of Gondwanaland; however, there are now two that are known: one is a benthic species in New Zealand (Wood et al, 2007), and the other is a thermophile from a hot spring in Kenya (Krientz et al, 2003).…”
Section: Worthwhile Areas For Further Researchmentioning
confidence: 98%